Association of burnout with stress, coping strategies and vocational satisfaction in Chilean clinical dental students. - Francisco Pérez; Pablo Caro; Bárbara Valenzuela; Jorge Ortiz; Juan Narvaez (Universidad de Concepción., 2016)
Objective: Dental students are particularly affected by stress, which can lead to 'burnout syndrome' by association with other psychological factors. The aim of this study was to analyse the effect of perceived stress, coping strategies, and vocational satisfaction on the severity of burnout in Chilean dental students in the clinical years. Method: The study population was comprised of clinical dental students of five Chilean dental schools. The following variables were considered: age, gender, year of study, burnout, coping strategies, perceived stress, and vocational satisfaction. Statistical analysis included descriptive measures, correlation tests, and stepwise multiple regression analysis. Results: The final sample included 244 students. Three (1.23%) students did not have burnout in any of its factors and 38 (15.57%) had severe levels in all three factors. There was a statistically significant greater 'emotional exhaustion' in 4th year students. There was a statistically significant correlation of the three factors of burnout with 'social withdrawal' coping strategy, high levels of perceived stress, and low levels of present and future vocational satisfaction. Conclusion: Most students presented moderate and high levels of burnout. This situation is associated with dysfunctional coping strategies, high levels of perceived stress, and low levels of present and future vocational satisfaction.